PRODUCT QUALITY AND CUSTOMER SATISFACTION AND THEIR EFFECT ON CONSUMER LOYALTY - Ernest Grace; Rosita Manawari Girsang; Sudung Simatupang; Vivi Candra; Novelyn Sidabutar (Bajang Institute, 2021)
The results of this study are to see whether the influence of product quality and customer satisfaction on consumer loyalty is found at Mandiri Jaya Mobil Pematangsiantar whose business is engaged in buying and selling new and used cars, with a total of 130 consumers and using validity, reliability, normality test, and analysis instruments. the coefficient of determination, as well as simple and multiple regression equations as well as the t hypothesis test and F test. Then a conclusion is generated that for the partial hypothesis answer it is found that the influence of product quality variables has a positive and significant effect on consumer loyalty then consumer satisfaction has a positive and significant effect on consumer loyalty and for the simultaneous test to produce answers to the hypothesis that simultaneously there is a positive and significant influence on product quality and consumer satisfaction on consumer loyalty. This shows that when product quality is getting better, and satisfaction is achieved, loyalty will persist.